2012
DOI: 10.1007/s10875-012-9746-4
|View full text |Cite
|
Sign up to set email alerts
|

Th2 Responses in OVA-Sensitized BALB/c Mice Are Down-Modulated By Mycobacterium bovis BCG Treatment

Abstract: BCG treatment inhibits features of allergic airway inflammation and the results suggest that the mechanism underlying the down-regulatory effects of BCG on OVA-induced airway inflammation appear to be associated with the induction of both Th1 and T regulatory immune responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…Serum was separated from blood samples obtained 24 hr and 48 hr after the last challenge. Anti‐OVA‐specific IgE and IgG2a were determined on serum, by optical density measurement at 492 nm in a microplate reader (SpectraMax 190; Molecular Devices, Sunnyvale, CA), as described elsewhere …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum was separated from blood samples obtained 24 hr and 48 hr after the last challenge. Anti‐OVA‐specific IgE and IgG2a were determined on serum, by optical density measurement at 492 nm in a microplate reader (SpectraMax 190; Molecular Devices, Sunnyvale, CA), as described elsewhere …”
Section: Methodsmentioning
confidence: 99%
“…Eosinophil peroxidase activity in lung homogenates was determined as described elsewhere. 21 To evaluate MPO, activity equal parts of homogenate supernatant and Ophenylenediamine solution in 10 mM citrate (pH 5Á5), followed by the addition of H 2 O 2 (20%). The reaction was stopped with H 2 SO 4 , and the absorbance was measured at 492 nm on a microplate reader (SpectraMax 190).…”
Section: Eosinophil Peroxidase and Myeloperoxidase Activitymentioning
confidence: 99%
“…Mice that received 3 labiar Ox challenges following sensitization showed an increase in eosinophil peroxidase activity in the labiar tissue at 24 hours and 120 hours (A); to measure eosinophil peroxidase activity (EPO), we adapted previously described methods [56,57]; excised labia were preserved at -80°C in 0.5% hexadecyltrimethyl ammonium bromide in phosphate-buffered saline, homogenized, freeze-thawed three times, centrifuged twice, first at 4750 rpm and next at 14000 rpm for 4 minutes at 4°C, and 50µl of the supernatant mixed with 100µl of 16mM o-phenylenediamene, 50mM-Tris-HCL, 0.01% H 2 O 2 . The reaction was stopped with 1M H 2 SO 4  after 15 minutes and OD measurements taken at 490 nm.…”
Section: Supporting Informationmentioning
confidence: 99%
“…It has been suggested that the inability of BCG revaccination to modulate atopic responses may be related to an individual's age at the time of antigen exposure and/or the genetic background of the study subjects 2 . In animal models, the effect of the modulation of the Th2 response was protective and improved parameters related to allergic conditions in animals exposed to microbial antigens before allergen sensitization 5 . Children with respiratory allergies who received neonatal BCG in Salvador were protected against asthma 8 .…”
Section: A B C D E Fmentioning
confidence: 99%
“…Nevertheless, there is increasing evidence that BCG vaccination modulates several aspects of atopy in experimental models of asthma and humans 4 . Mice immunized with BCG and sensitized intranasally with ovalbumin (OVA) had a lower percentage of eosinophils in the bronchoalveolar lavage, reduced levels of total and allergenspecific serum immunoglobulin E (IgE), decreased levels of T-helper 2 (Th2) cytokine, decreased lung inflammation, as well as increased levels of interferon gamma (IFN-γ), tumor necrosis factor beta (TGF-β), and interleukin-10 (IL-10) 5 . Increased levels of allergen-specific serum IgE and eosinophilia are hallmarks of atopic asthma, and the former is correlated with the severity of clinical symptoms 6 .…”
mentioning
confidence: 99%